Genomic structure, promoter activity, and developmental expression of the mouse homologue of the Machado–Joseph disease (MJD) gene - Costa, Maria do Carmo (2004)
Machado–Joseph disease (MJD) is a neurodegenerative disorder, caused by the expansion of the (CAG)n tract in the MJD gene. This encodes the protein ataxin-3, of unknown function. The mouse Mjd gene has a structure similar to that of its human counterpart and it also contains a TATA-less promoter. Its 5V flanking region contains conserved putative binding regions for transcription factors Sp1, USF, Arnt, Max, E47, and MyoD. Upon differentiation of P19 cells, the Mjd gene promoter is preferentially activated in endodermal and mesodermal derivatives, including cardiac and skeletal myocytes; and less so in neuronal precursors. Mouse ataxin-3 is ubiquitously expressed during embryonic development and in the adult, with strong expression in regions of the CNS affected in MJD. It is particularly abundant in all types of muscle and in ciliated epithelial cells, suggesting that it may be associated with the cytoskeleton and may have an important function in cell structure and/or motility.